The Potential for Organic Matter and Nutrient Recovery from Broccoli Harvest Residues to Support Sustainable Agriculture - Tria Suci Astira; Tittan Triken Mardhika; Ismail Saleh; Ray March Syahadat (Agricultural Science, 2025)
The return of harvest residues to the soil is an essential strategy in supporting sustainable agriculture, particularly for horticultural commodities such as broccoli (Brassica oleracea var. italica). This study aims to analyze the potential return of organic matter and macronutrients (N, P, K) as well as organic carbon (C-organic) from broccoli harvest residues to enhance soil fertility and reduce dependence on chemical fertilizers. The research was conducted in May 2025 in Desa Tani, Cipanjalu, Cilengkrang, Bandung Regency, with laboratory testing performed at the Department of Agronomy and Horticulture, IPB University, Bogor. A quantitative and descriptive approach was employed through observation, interviews, and laboratory analysis. The identification results showed that the total fresh weight of broccoli plants was 1,169 grams, of which only 400 grams were harvested, while the remaining 769 grams consisted of leaves, lower stems, and roots left in the field. The dry weight of the harvest residues was 77 grams per plant. With a planting density of 22,000 plants per hectare, the potential nutrient return was calculated using the formula: Nutrient Return = Dry Weight × Nutrient Content × Population per hectare. The nutrient content analysis showed that the broccoli residues contained 7.03% nitrogen (N), 0.90% phosphorus (P), 4.84% potassium (K), and 33.79% organic carbon (C-organic). Broccoli harvest residues have been proven to possess significant nutrient value and can be utilized as green manure to improve soil structure and reduce the use of synthetic fertilizers.